First Record of the Holarctic and Northern Oriental Genus Gymnopternus Loew (Diptera: Dolichopodidae, Dolichopodinae) near the Equator: Description of a New Species from a Swamp Forest in Singapore - Grootaert, Patrick (Tropical Natural History, 2020)
The genus Gymnopternus Loew, 1857 is recorded for the first time in Singapore. It is the southernmost record of the genus in the Oriental Realm until now. The new species Gymnopternus ghufrani sp. nov. is described and illustrated. It is recorded from a mature swamp forest in the Kranji Marshes reserve that was previously part of a mangrove system. This area turned into a freshwater swamp, with lakes and secondary forests after the closure of the Kranji reservoir in the seventies.